Does the right to work part-time affect mothers' labor market outcomes? - Hannah Paule-Paludkiewicz (Deutsche Bundesbank, 2024)
This paper studies how the statutory right to work part-time affects mothers' post-birth labor market outcomes. I use a differences-in-differences design to investigate a reform in Germany that granted the right to work part-time to employees of firms with more than 15 employees. I find that the reform increased the probability of eligible mothers working part-time in the short run after childbirth, indicating that the law relaxed a binding constraint. In the longer run, the reform had a positive effect on maternal employment and labor income, but did not change part-time status significantly.
Keywords: J13; J18; J22; J83; 330; Female Employment; Part-Time Work; Fertility; Family and Work Obligations